Enhancing the Livelihoods of the Rural Poor through ICT - A Knowledge Map : Tanzania Country Study - Economic and Social Research Foundation (World Bank, Washington, DC, 2015)
The major objective of the study was to come up with illustrative success stories as well as failures to give lessons on ICT interventions in the area of rural livelihoods and their impact in Tanzania. The key issues addressed in this study were: 1) common ICTs used by the rural poor in Tanzania; 2) which ICTs are regarded as attractive by different groups and why; 3) the use of ICTs by different age cohorts as part of their livelihoods strategies; 4) the role of ICTs in influencing the livelihoods of the poor; 5) what effects, if any, does use of these resources have on vulnerability, livelihoods and value of assets; and 6) whether or not ICT services can be improved in relation to their usage and effects. The study also made a comparative analysis of the use of ICTs by different groups based on age, location, gender and ethnicity. This study was conducted for a period of four months from October 2006 to January 2007, in three different districts (Bagamoyo, Moshi Rural and Njombe). The findings from this study reveal that ICTs commonly used by the rural poor in the selected districts are radio, mobile phone and TV. Development of ICTs is a result of a number of interventions by government, NGOs, development partners and the private sector, and this has impacted on the livelihoods of the rural poor. Survey results confirmed this by revealing that ICTs contributed to improving rural livelihoods through improved businesses (17%), increased access to education (3%), ease of communications (50%) and increased access to key information (30%). The output of this study is expected to inform policymakers as well as other stakeholders, such as development partners, civil society and the private sector, on how ICTs can be adapted to help improve the livelihoods of poor individuals, families and communities in rural areas and increase their income opportunities and/or livelihood sources, thereby improving their chances of escaping from persistent poverty. It also documents what has already been implemented in Tanzania as far as ICTs and rural livelihoods are concerned, and the pertinent gaps in terms of improving the livelihoods of the rural poor by using ICT tools.